Study of Rsm/Gac post-transcriptional regulation by quorum sensing, extracellular and intracellular signals in Pseugomonas aeruginosa - Righetti, Karima Maria (2011)
Bacteria have evolved ways to sense and respond to changes in their population density through quorum sensing (QS) systems, and to adapt to changes in the extracellular environment through two component systems (TCS). In Pseudomonas aeruginosa, QS and the GacS/GacA TCS are global regulatory systems that modulate the expression of virulence genes at the transcriptional and post-transcriptional level, respectively. Although in P. aeruginosa the QS network has been extensively characterized, the way the Gac/Rsm global regulatory system is regulated is still unclear. The study of QS and Gac/Rsm networks is crucial for the development of new drugs able to interfere with these regulatory systems. This thesis is dedicated to the study of the Gac/Rsm global regulatory system and its interaction with the QS network. An introduction to these systems is presented in Chapter 1. The materials and methods used in this study are described in Chapter 2. In Chapter 3 the methods to detect and identify the extracellular signals modulating Gac/Rsm system are investigated. This analysis led to the identification of the Pseudomonas Quinolone Signal (PQS) molecule, which is responsible for the activation of the gene coding for the small RNA RsmZ. RsmZ (in synergy with RsmY) antagonises by titration the effects of the global post-transcriptional regulator RsmA, a small RNA-binding protein which targets specific mRNAs. Since the discovery of QS, there have been many studies showing the importance of this type of regulatory mechanism in the global transcriptional control of gene expression. However, there has been no clear evidence to attribute to QS a key role in post-transcriptional regulation of terminal gene targets. In Chapter 4, the importance of PQS in the control of lecA is demonstrated. lecA encodes for the PA-I galactophilic lectin protein whose translation rates is modulated by the activity of the regulatory small RNA rsmZ in concert with RsmA. These results demonstrate that QS not only controls terminal target gene expression at the transcriptional level, but also at the translational level. Using a genetic bank, a transposon mutagenesis and a promoter pull-down approach, new regulators were identified together with regulatory networks involved in the modulation of the global Gac/Rsm system. These results are described in Chapter 5. Chapter 6 is focused on the effect of a library of compounds available in our laboratory, for their QS-inhibiting potential. The conclusions and future directions are presented in Chapter 7.